Studies on the bioactive properties of selected plant and fermented extracts / Saravana Kumar Sinniah - Kumar Sinniah, Saravana (2010)
The aim of this study was to isolate protein/peptide and secondary metabolites from plant and fermented sources. The extracts were used to test for antimicrobial and antioxidant properties. In the current study protein/peptide extracts of Allium sativum showed promising results with a 15mm inhibition zone against Escherichia coli, 28mm against Staphylococcus aureus, 16.3mm against Bacillus cereus and 9mm against Pseudomonas aeruginosa. The minimum bacteriocidal concentration (MBC) results showed that Allium sativum protein/peptide extract is only bacteriostatic and not bacteriocidal. Andrographis paniculata showed the most promising result for the ethanolic extracts with an inhibition zone of 14mm against B. cereus, 11.5mm against P. aeruginosa, and 11mm against S. aureus. Ethanolic extract of Andrographis paniculata showed minimum inhibitory concentration (MIC) and MBC values below 10mg/ml for both B. cereus and S. aureus. This result proves that Andrographis paniculata extract at a concentration of 10mg/ml is both bacteriostatic and bacteriocidal. Ethanolic extract of Cymbopogon citratus exhibited high antioxidant properties. Toxicity studies on all four plant extracts namely Andrographis paniculata, Curcuma mangga, Cymbopogon citratus and Allium sativum did not reveal any toxic symptoms or mortality at 2500mg/kg doses. The selected plant extracts were fractionated with HPLC on a C-18 reverse phase column. The fractions collected were used for matrix-assisted laser desorption/ionization (MALDI) Time of Flight TOF/TOF analysis.